Selection and analysis of a predictive model to forecasting sales in projects of winning management consultancy - Oliveira, Ana Filipa dos Santos de (2015)
Winning Management Consulting (WMC) is a Management Consulting Company, certified and accredited. It is a company that provides services to other companies, so it is strongly dependent on sales and clients that buy their services. Have the ability to predict which are the factors that clients have in mind when decide to accept or refuse a proposal done by a consulting company, can give an enormous competitive advantage to company reach the success. It was the objective of this study analyses and determines which are the factors that affect the clients’ decision of accept or refuse a proposal of WMC. To do that it was invited experts to participate in the study and define, in their opinion, which are the factors that might affect those decisions. A selection of the factors using correlation analysis was done and the 183 proposals of the sample were classified across those factors. A multiple regression analysis between the defined factors (independent variables) and the result (dependent variable - acceptance or non-acceptance proposal) was done to select the five factors that better explain the total variation of the result. The results allow to conclude that the five factors are: Technical Credibility in Proposal Phase, Budget Availability, Knowledge of Clients Target Price, Competitive Price and Interlocutor Benefits. An analysis of the results allows to provide to WMC a path of how to lead the negotiations with clients in order to reach a successful result, which means the acceptance of the WMC proposal.